2022
DOI: 10.31635/ccschem.021.202101333
|View full text |Cite
|
Sign up to set email alerts
|

Diradicals or Zwitterions: The Chemical States of m -Benzoquinone and Structural Variation after Storage of Li Ions

Abstract: m-Benzoquinones are often regarded as unstable materials in the form of radicals. Herein, an air-stable small molecular m-benzoquinone (4,6-diamino-1,3-benzoquinone (4,6DA1,3BQ)) without bulky groups or large conjugated systems are reported and its chemical structure and state are profoundly elucidated by a series of substantial investigations, indicating the presence as zwitterions rather than diradicals. The deep study indicated that the m-benzoquinone structure of 4,6DA1,3BQ was stabilized through the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…[15][16][17][18][19][20] More importantly, organic electrodes have particularly suitable redox potentials for aqueous electrolytes, which could be adjusted facilely through molecular design. [21][22][23][24][25][26][27][28][29][30][31][32] Furthermore, the weak intermolecular interactions could enable the rapid diffusion and storage of large-sized or multi-valent ions, [15,[33][34][35][36][37][38][39] which make organic materials more meaningful for ZIBs. However, organic ZIBs are in their infancy and are still suffering the limited capacity and poor cyclability.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] More importantly, organic electrodes have particularly suitable redox potentials for aqueous electrolytes, which could be adjusted facilely through molecular design. [21][22][23][24][25][26][27][28][29][30][31][32] Furthermore, the weak intermolecular interactions could enable the rapid diffusion and storage of large-sized or multi-valent ions, [15,[33][34][35][36][37][38][39] which make organic materials more meaningful for ZIBs. However, organic ZIBs are in their infancy and are still suffering the limited capacity and poor cyclability.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic peak of the C=O bond in FT‐IR spectra apparently weakened while the C–O bond strengthened upon storage of Li + ions and recovered back after charge (Figure 3g), indicating the typical redox reaction of carbonyl groups. [ 24,35 ] The intensity variation of the C=O bond in the ex situ Raman spectra (Figure S13, Supporting Information) and O 1 s XPS spectra (Figure S14, Supporting Information) displayed a similar tendency. These results were in good agreement with the charge storage mechanism of carbonyl groups.…”
Section: Resultsmentioning
confidence: 79%
“…CCDC 227509), [ 34 ] demonstrating the same molecular arrangement with the reported single crystal structure (Figure 1d). [ 35 ] In the crystal lattice, two types of intermolecular hydrogen bonds (Figure 1e) and π‐π stacking interactions exist. [ 34 ] Benefiting from the strong intermolecular interactions, the POxa could maintain stable up to a temperature near 300 °C that is unusually high for small molecules (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
“…44,45 Moreover, the difference between oxidation and reduction decreased after cycling, which indicated the smaller polarization and the easier storage after cycling and hence indicated that the initial stress of storage of large sized anions decreased, which should be ascribed to the possible activation process. 46,47 The CV curve became stable afterwards, indicating the reversibility of BDBDT electrodes. The galvanostatic charge–discharge profiles of the BDBDT cathode material in the same potential window at a current density of 0.5 A g −1 are shown in Fig.…”
mentioning
confidence: 94%